VD_FINDINFO 259/II vom 23. Dezember 2009 - VD Tribunal cantonal (2009)
DÉTENTION AUX FINS D'EXPULSION, RISQUE DE FUITE, PROPORTIONNALITÉ | 76 al. 1 let. b ch. 3 LEtr, 76 al. 1 let. b ch. 4 LEtr, 80 al. 1 LEtr, 80 al. 6 LEtr, 30 LVLEtr, 31 LVLEtr